Start-Up Phase Performance of a Basic Water Purification System for Urban Surface Water Treatment - Endah Lestari; Dede Rohmat; Wati Asriningsih Pranoto; Muhammad Sofyan; Arief Suardi Nur Chairat (Politeknik Siber Cerdika Internasional, 2026)
Background: The increasing degradation of urban surface water quality due to suspended solids, dissolved metals, and anthropogenic activities has driven the demand for simple, cost-effective, and sustainable water treatment technologies. Methods: This study evaluated a Basic Water Purification System (BWPS) during its start-up phase, examining water quality changes associated with the stabilization of newly installed filtration media. Surface water from a retention pond was treated using a multi-media filtration system consisting of zeolite, silica sand, activated carbon, anthracite, manganese sand, and ion exchange resin across three configurations. Temperature, total dissolved solids (TDS), turbidity, color, pH, nitrate, nitrite, Fe, and Mn concentrations were assessed at three sampling points. Results: TDS, turbidity, color, Fe, and Mn concentrations increased after filtration, resulting in negative removal efficiencies attributable to initial leaching from the newly installed media. However, TDS, Fe, and Mn concentrations consistently declined from the first to the third sampling point, indicating progressive media stabilization. Media 2 demonstrated the most consistent performance, maintaining a near-neutral pH range (6.3–7.2) and the lowest TDS levels, while Media 3 achieved the highest Fe removal efficiency (13.53%). Correlation analysis revealed strong positive relationships between TDS and dissolved metal concentrations, as well as between turbidity and color, confirming that these fluctuations were associated with media conditioning rather than inadequate treatment performance. Conclusion: These findings confirm that the Basic Water Purification System (BWPS) is a promising low-cost, decentralized option for urban surface water treatment, provided that an adequate media conditioning period is implemented before full-scale operation.